Evaluating the impact of development projects on poverty : a handbook for practitioners - Baker, Judy L. (Washington, D.C. : World Bank, 2000)
This handbook seeks to provide project managers and policy analysts with the tools needed for evaluating project impact. It is aimed at readers with a general knowledge of statistics. For some of the more in-depth statistical methods discussed, the reader is referred to the technical literature on the topic. Chapter 1 presents an overview of concepts and methods. Chapter 2 discusses key steps and related issues to consider in implementation. Chapter 3 illustrates various analytical techniques through a case study. Chapter 4 includes a discussion of lessons learned from a rich set of ""good practice"" evaluations of poverty projects which have been reviewed for this handbook.
Includes bibliographical references (p. 83-93).
rpm 21/09/16, ijb 21/02/2019
Loans
Keywords: Economic development projects; Economic development projects -- Evaluation; Poor; Poor -- Developing countries